Paryavarna Sakhi : Enabling Women-Led Waste Management and Social Entrepreneurship for Sustainable Development - Nayak, Venkatesha; Hegde, Kavya P. (AMC Indian Journal of Entrepreneurship, 2023)
Purpose : This paper proposed the role of the â€œParyavarna Sakhiâ€ model in empowering women to lead waste management initiatives and thus contribute to social entrepreneurship, which also emphasizes sustainable development. Methodology : The research study considered a comprehensive approach, where the studies on waste management, womenâ€™s empowerment, and social entrepreneurship were reviewed to create a model. This research considered multifaceted aspects of the â€œParyavarna Sakhiâ€ model. It assessed key dimensions such as active participation of members, leadership encouragement, gender equality, and economic empowerment. Findings : This study shed light on how women fit into the â€œParyavarna Sakhiâ€ model framework for trash management. Positive influences were economic empowerment, leadership promotion, and active involvement; gender equality was crucial. Practical Implications : It is recommended that individuals and organizations embrace the tenets of the â€œParyavarna Sakhi modelâ€ by encouraging the active engagement of women as stakeholders and the spread of reliable information. The study acknowledged its limitations and suggested directions for further investigation. Originality : This study was the first to examine womenâ€™s empowerment in waste management via the distinctive perspective of the Paryavarna Sakhi model, in contrast to previous studies on social entrepreneurship and women entrepreneurship. It gave the conversation about sustainable development a fresh viewpoint.